Барчукова Наталия Кировна (Москва). Бирюков Павел Николаевич (Воронеж). Гаврилов Вячеслав Вячеславович (Владивосток). Павлова Людмила Васильевна (Минск). Па нов Владимир Петрович (Москва). Сафин Фаниль Масгуто- вич (Уфа). Скачков Никита Геннадьевич (Москва). Ровней- ко Вера Владимировна (Ижевск) (Московский журнал международного права, 1999)
.